2020
DOI: 10.1590/s0102-865020200050000002
|View full text |Cite
|
Sign up to set email alerts
|

Changrui enema inhibits inflammation-induced angiogenesis in acute radiation proctitis by regulating NF-κB and VEGF

Abstract: Purpose Changrui enema, a traditional Chinese medicine prescription, is used as a supplementary treatment for acute radiation proctitis (ARP). Herein we explored the inhibition effects of Changrui enema on NF-κB and VEGF in ARP mice. Methods A total of 120 C57BL/6 mice were divided randomly into normal mice group, ARP mice group, western medicine enema group (dexamethasone combined with gentamicin), and Changrui enema group. ARP mice were established by pelvic local irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Spleen is the largest lymphoid organ 62 and modulates the immune system by producing lymphocytes, immunoglobulin and complement, etc. Our previous study found that DXM + GM enema reduced spleen weight and promoted lymphocyte apoptosis by increasing Bax and suppressing Bcl-2 5 . We propose that apoptosis induction of DXM + GM may be an organ-specific effect.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Spleen is the largest lymphoid organ 62 and modulates the immune system by producing lymphocytes, immunoglobulin and complement, etc. Our previous study found that DXM + GM enema reduced spleen weight and promoted lymphocyte apoptosis by increasing Bax and suppressing Bcl-2 5 . We propose that apoptosis induction of DXM + GM may be an organ-specific effect.…”
Section: Discussionmentioning
confidence: 93%
“…As everyone knows, VEGF is one of the most key cytokines in promoting angiogenesis 24 . Studies 5,21 have demonstrated that the high expression of VEGF is related to angiogenesis in ARP. Here, we put forward a hypothesis that "inflammation-induced angiogenesis" exists in pathogenesis of ARP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations